Challenges and Potential of Blue Economy in Supporting Sustainable Development in Luwu Raya - Amir, Rismayanti (International Publisher (YAPENBI), 2025)
The Blue Economy and Sustainable Development are two interrelated concepts that mutually reinforce one another. Both hold great potential, especially in regions like Luwu Raya, which has rich marine and coastal resources. However, the practical implementation of the blue economy faces a number of significant challenges. This research aims to explore the potentials and barriers to realizing sustainable development through the blue economy in Luwu Raya. The study employs field research using a descriptive qualitative approach. Data were collected through purposive sampling, selecting participants based on criteria most relevant to the research objectives. The analysis technique utilized is content analysis, which allows for in-depth and systematic examination of various data sources. Data triangulation was also conducted to ensure the validity of the findings. The results indicate that while Luwu Raya has promising marine and fishery resources, several key challenges hinder progress. These include limited innovation in processing marine products into high value-added commodities, low public awareness and literacy regarding environmental sustainability, and minimal adoption of eco-friendly technologies. Although the use of simple fishing gear is environmentally sustainable, it does not contribute significantly to economic growth, thus falling short of blue economy principles. Among all challenges, waste management and environmental pollution emerge as the most pressing issues, as they impact the economic, social, and ecological dimensions of sustainable development. Addressing this through circular economy strategies and targeted government policies could generate employment, boost local incomes, and reduce pollution— ultimately supporting the realization of sustainable development in Luwu Raya.